2018
DOI: 10.1186/s13046-018-0917-x
|View full text |Cite
|
Sign up to set email alerts
|

GLI2 promotes cell proliferation and migration through transcriptional activation of ARHGEF16 in human glioma cells

Abstract: BackgroundThe Hedgehog (Hh) signaling pathway plays critical roles in modulating embryogenesis and maintaining tissue homeostasis, with glioma-associated oncogene (GLI) transcription factors being the main mediators. Aberrant activation of this pathway is associated with various human malignancies including glioblastoma, although the mechanistic details are not well understood.MethodsWe performed a microarray analysis of genes that are differentially expressed in glioblastoma U87 cells overexpressing GLI2A, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 66 publications
3
30
0
Order By: Relevance
“…24 In human glioma cells, it also has been suggested that GLI2 promotes cell proliferation and migration through transcriptional activation of ARHGEF16. 25 These results are consistent with our data, compared to CAL27 cells, CAL27-MDR showed lower expression of GLI2 with decreased proliferation ( Figure 2C and Figure S3). It is reasonable that comprehensive pathways might regulate the activation of GLI2 in OSCC-MDR, and investigations should be conducted to gain further insight.…”
Section: Discussionsupporting
confidence: 92%
“…24 In human glioma cells, it also has been suggested that GLI2 promotes cell proliferation and migration through transcriptional activation of ARHGEF16. 25 These results are consistent with our data, compared to CAL27 cells, CAL27-MDR showed lower expression of GLI2 with decreased proliferation ( Figure 2C and Figure S3). It is reasonable that comprehensive pathways might regulate the activation of GLI2 in OSCC-MDR, and investigations should be conducted to gain further insight.…”
Section: Discussionsupporting
confidence: 92%
“…FGF19, the human ortholog of FGF15, is essential for embryonic brain development 41 and overexpression of FGF19 is implicated in breast cancer progression and metastasis 42 . ARHGEF16 was recently shown to promote glioma cell migration and proliferation 22 . Upregulation of these GLI2 target genes by TGLI1 further contributes to the aggressiveness of TGLI1.…”
Section: Discussionmentioning
confidence: 99%
“…6D). We next examined whether TGLI1 regulates expression of GLI2 target genes [22][23][24] and found TGLI1 to upregulate GLI2 target genes to a higher extent than GLI1 ( Supplementary Fig. 3E).…”
Section: Tgli1 Upregulates Stemness Genes In Breast Cancer Cellsmentioning
confidence: 99%
“…The more significant suppressive effects of miR-29a/b/c-3p on STAT3 than on Gli2 as well as the complete rescue effects of Gli2 on circ-STAT3-mediated cell functions aroused our interest. It has been verified that circRNAs and their host genes could be regulated by the common transcription factor [23], and Gli2 was previously reported as the transcription factor to activate upregulation of its downstream genes [24]. We wondered whether Gli2 transcriptionally activated STAT3 and further up-regulated circ-STAT3.…”
Section: Gli2 Transcriptionally Activated Stat3mentioning
confidence: 89%